Exploring Students’ Attitudes and Insight toward the Changing Face of AIDS - Egli, Eric; Movahedzadeh, Farahnaz; Greer, Elisabeth Heard; Heldt, Marcus; Cherif, Abour H. (IJRDO- Journal of Educational Research, 2016)
The purpose of this undertaking is to gauge how students at a two-year college view HIV infection/AIDS, given that much has changed regarding this disease in the past decade. We have conducted a research study to discover where misinformation, discrimination, and stigma might exist in this community. A presentation, delivered by a guest speaker using his personal life experience and knowledge, was used to educate students in selected classes. We then administered a survey in order to research students’ attitudes and insights regarding this important topic using the cluster method. The survey also included data from students in the classes who were exposed to the presentation and its insight before they took the survey. The preliminary analysis of this data reveals that there is a disconnect between the facts/science regarding HIV/AIDS and students’ attitudes and perceptions. In order for today’s students to be able to intelligently handle the responsibility of this highly important civic reality, it is essential that the HIV/AIDS curriculum is “reinvented” for all disciplines and presented to all college students so that they are armed with facts. We are in an era where treatment can equal prevention, yet our data is showing this is not understood. Having an understanding of the current science and social aspects of HIV/AIDS will spark debate, increase awareness, and ultimately reduce stigma and social discrimination that currently exists. It is important to give students the opportunity to become deep learners by engaging in active civic learning, which leads to a better understanding of, as well as long-term retention of, learned concepts.